Case report: Individualized treatment of advanced breast cancer with the use of the patient-derived tumor-like cell cluster model - Xia, Wenjie; Chen, Wuzhen; Fang, Shan; Wu, Jun; Zhang, Jingxia; Yuan, Hongjun (Frontiers in Oncology, 2022)
Breast cancer is one of the most common tumors in women. Despite various treatments, the survival of advanced breast cancer is still disappointing. Furthermore, how to find effective individualized treatment for different kinds of patients is a thorny problem. Patient-derived tumor-like cell clusters were reported to be used for personalized drug testing in cancer therapy and had a prediction accuracy of 93%. However, there is still lack of case reports about its application in the individualized treatment of breast cancer patients. Here, we described 4 cases of individualized treatment for advanced breast cancer with the use of patient-derived tumor-like cell clusters model (PTCs model). In these 4 cases, PTCs model showed a good predictive effect. The tumor size was reduced significantly, or even disappeared completely by clinical, radiological, or pathological evaluation with the help of PTCs model for selecting individualized therapy regimen. Furthermore, the drug sensitivity test results of PTCs model were consistent with pathological molecular typing and the actual clinical drug resistance of the patients. In summary, our case reports first evaluated the application value of PTCs model in advanced breast cancer, and PTCs model might be used as an efficient tool for drug resistance screening and selecting better personalized treatment, though further study is needed to prove the validity and stability of PTCs model in drug screening.